Investigation of PD-L1 Biomarker Testing Methods for PD-1 Axis Inhibition in Non-squamous Non–small Cell Lung Cancer. (October 2016) - Sheffield, Brandon S.; Fulton, Regan; Kalloger, Steve E.; Milne, Katy; Geller, Georgia; Jones, Martin; Jacquemont, Celine; Zachara, Susanna; Zhao, Eric; Pleasance, Erin; Laskin, Janessa; Jones, Steven J.M.; et al.
Inhibitors of the programmed cell death 1 (PD-1) signaling axis have recently demonstrated efficacy and are rapidly being incorporated into the treatment of non–small cell lung cancers (NSCLCs). Despite clear benefits to certain patients, the association of these responses with a predictive biomarker remains uncertain. Several different biomarkers have been proposed, with differing results and conclusions. This study compares multiple methods of biomarker testing for treatment of NSCLCs with PD1-axis inhibitors. Tissue microarrays of matched primary and metastatic NSCLCs were used to compare four different PD-1 ligand (PD-L1) IHC techniques, as well as RNA ISH. Additional cases with whole genome and transcriptome data were assessed for molecular correlates of PD-L1 overexpression. Eighty cases were included in the IHC study. Multiple IHC methodologies showed a high rate of agreement (Kappa = 0.67). When calibrated to RNA expression, agreement improved significantly (Kappa = 0.90, p =0.0049). PD-L1 status of primary and metastatic tumors was discordant in 17 (22%) cases. This study suggests that different IHC methodologies for PD-L1 assessment provide slightly different results. There is significant discordance between the PD-L1 status of primary tumors and lymph node metastases. RNA ISH may be a useful adjunct to complement PD-L1 IHC testing.